2010
DOI: 10.1007/s11148-010-9307-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of type of high-alumina cement on the properties of heat-resistant concrete with a composite deflocculant

Abstract: Differences are demonstrated in hydration of high-alumina cements, produced in the Gor'ka Plant (Poland), in the presence of both individual and composite deflocculants. Properties are provided for medium-cement heat-resistant concrete with a composite deflocculant in relation to cement type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Ma Chao [17] studied the effect of polyester fibres on the heat resistance of concrete, the study concluded that the high temperature of the fibres melted to form pores is conducive to moisture dissipation, reducing the production of internal defects in concrete, and the best number of fibres for 2 kg/m3. Antonovich [18] claimed that the admixture compound in concrete can significantly improve the heat resistance of concrete. Domestic and foreign scholars from the cementitious materials, aggregates, fibres, admixtures and other aspects, trying to reduce the difference in thermal expansion properties of different materials, improve the connected pores, hinder the expansion of cracks and other points to improve the thermal performance of concrete [19][20].…”
Section: Status Of Research Use Of Heat Resistant Concretementioning
confidence: 99%
“…Ma Chao [17] studied the effect of polyester fibres on the heat resistance of concrete, the study concluded that the high temperature of the fibres melted to form pores is conducive to moisture dissipation, reducing the production of internal defects in concrete, and the best number of fibres for 2 kg/m3. Antonovich [18] claimed that the admixture compound in concrete can significantly improve the heat resistance of concrete. Domestic and foreign scholars from the cementitious materials, aggregates, fibres, admixtures and other aspects, trying to reduce the difference in thermal expansion properties of different materials, improve the connected pores, hinder the expansion of cracks and other points to improve the thermal performance of concrete [19][20].…”
Section: Status Of Research Use Of Heat Resistant Concretementioning
confidence: 99%